Refer to the graph below.
Work Step by Step
Solve for $y$. Add $y$ and subtract $2$ to both sides for the equation: $3x-y+y-2=2+y-2 \\3x-2=y \\y=3x-2$ This means that the given equation is equivalent to $y=3x-2$. To graph the equation, perform the following steps: (1) Create a table of values by assigning $-2, 0,$ and $2$ to $x$ then solving for the corresponding value of $y$ of each one. (refer to the attached image below for the table) (2) Plot each point and connect them using a line. (refer to the attached image in the answer part above for the graph)